The Kashmir question : retrospect and prospect - Ganguly, Sumit (Frank Cass, 2003)
Few bilateral conflicts have proven as resistant to resolution as the Kashmir disputebetween India and Pakistan. What explains the tenacity of this dispute? The answer iscomplex and goes to the very basis of state-construction in South Asia. India, which hadbeen created as a civic polity, initially sought to hold on to this Muslim-majority state todemonstrate its secular credentials. 1 Pakistan, in turn, had laid claim to Kashmir becauseit had been created as the homeland for the Muslims of South Asia. 2 After the break-up ofPakistan in 1971 the Pakistani irredentist claim to Kashmir lost substa.